Inconsistent and Imprecise Explanations: NYT v Commission, Transparency, and the Search for Lost Documents - Pielpa Ollikainen (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2025 10(2), 451-462 | Article | (Series Information) European Papers - A Journal on Law and Integration, 2025 10(2), 451-462 | Article | (Table of Contents) 1. Introduction. – 2. Background. – 3. Judgment of the General Court. – 3.1. Against a narrow reading of possession. – 3.2. Obligation to provide plausible explanations. – 3.3. Document registration. – 4. Plus ça change. – 4. Conclusion. | (Abstract) On May 14, 2025 the Grand Chamber of the General Court handed down its judgment in T-36/23 Stevi and the New York Times Company (NYT) v European Commission. The eagerly-awaited judgment is an unequivocal win for proponents of EU institutional transparency. The Court made short shrift of the Commission’s evasive justifications for refusing access to the requested documents and clarified the core concepts that define the scope of the access to documents regime of Regulation 1049/2001. The judgment clarifies the concept of possession, so as to discourage tactical deletion of documents by institutions, and elaborates on their obligation to provide an explanation for why the requested documents could not be found. Both are linked to the duty of the institutions to proactively promote transparency via document retention practices.